The Influence of Tourist Motivation on Visiting Decision at Banto Royo, Tourism Destination in Agam Regency - Agustin, Sindi Afriani; Asnur, Lise (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
This research was conducted against the backdrop of several issues, such as a lack of visitor engagement, underutilized tourist attractions, subpar services, and exorbitant ticket prices. The objective of this study was to investigate the impact of Tourism Motivation on the decision to visit the Banto Royo Tourism Destination in Agam Regency. The research methodology employed herein is quantitative, and employs causal-associative methods using purposive sampling techniques. Data collection was conducted by disseminating questionnaires to 96 individuals who had previously visited the Banto Royo tourism site in Agam Regency. The validity and reliability of the questionnaire were verified using SPSS version 24. Results from the study revealed the following: (1) Tourism Motivation falls within the